PERDAMAIAN DAN HARMONI DALAM PERSPEKTIF PENDIDIKAN - Aunurrahman Aunurrahman (State Islamic University North Sumatra, 2008)
Abstract: Peace and Harmony in the Perspective of Education. Education for peace and harmony is a teaching process in creating receiprocal understanding amongst students without prejudice and negative thinking that enables them to prevent emerging conflict. It has been well established that education is a fundamental foundation to internalize norms effectively for students as it is directly related to daily life of mankind. Thus, the author argues that to build students’ tolerant character, it is deemed necessary to create tolerant atmosphere in all level, wheteher in family, social or formal educadional level. This paper tries to analyze how to implement the peaceful, harmonious and tolerant values in teaching and learning process in the formal education, family as well as society. Kata Kunci: perdamaian, harmoni, dan pendidikan